Hematologic manifestations of coronavirus disease 2019 in children: Case-series report and a review - Grace Onimoe; Grace Onimoe; Juan Alvarado; Juan Alvarado; Anita Boakye (Frontiers Media S.A., 2022)
On 11 March 2020, coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus (SARS-CoV-2) was declared as a pandemic by the World Health Organization (WHO). As the COVID-19 pandemic has ravaged worldwide, children have not been unaffected. Information gleaned from adult experience with the disease has aided in disease detection and treatment strategies in children. Numerous cases have been described in adult literature about hematologic manifestations of COVID-19. This case series aims to report several hematologic presentations in patients with COVID-19 and multisystem inflammatory syndrome in children (MIS-C, an immune-mediated reaction leading to severe COVID-19 illness) with and without a primary hematologic disorder.